Diffusion tensor imaging findings of the brainstem in subjects with tonsillar ectopia - Kurtcan, SERPİL; KURTCAN, SERPİL; Alkan, ALPAY; ALKAN, ALPAY; YETIS, Huseyin; TÜZÜN, Umit; Aralasmak, AYŞE; ARALAŞMAK, AYŞE; Toprak, HÜSEYİN; TOPRAK, HÜSEYİN; Ozdemir, HÜSEYİN; ÖZDEMİR, HÜSEYIN (My University, 2018)
We aimed to evaluate the differences between apparent diffusion coefficient (ADC), fractional anisotropy (FA), axial diffusivity (AD), and radial diffusivity (RD) values obtained from different cranial sites in subjects with Chiari I Malformation (CM-I) and borderline tonsillar ectopia (BTE), and to determine correlations between diffusion tensor imaging (DTI) metrics and the severity of tonsillar ectopia. A total of 73 subjects with CM-I and BTE and 35 control underwent MRI and DTI. In our study, ADC values measured from the level of medulla oblongata and the RD values measured in middle cerebellar peduncles, thalamus, and globus pallidus were higher in CM-I patients than in controls. FA values at the medulla oblongata level and AD values at the medulla oblongata and pons level higher in patients with CM-I. ADC and AD values measured at the pons level were higher in BTE subjects than in controls. Compared with BTE, the CM-I subjects- ADC values at the medulla oblongata and AD values at the pons level were higher. In addition, FAs at the pons and medulla oblongata level were higher. At the medulla oblongata level, a positive correlation was observed between ADC and the size of tonsillar ectopia. AD and FA values measured at the level of medulla oblongata and pons were positively correlated with the size of tonsillar ectopia. These findings may be related to the severity of microstructural changes involving neuronal tracts at the brainstem level due to tonsillar ectopia. DTI may be useful in determining the extent of microstructural changes at the tissue level in subjects with tonsillar ectopia.